Efficacy of regorafenib in the second-and third-line setting for patients with advanced hepatocellular carcinoma: A real life data of multicenter study from Turkey - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2020)
Purpose: After failure of the first-line sorafenib treatment in advanced or metastatic stage hepatocellular carcinoma (HCC), regorafenib is one of the newly-approved targeted agents. We aimed to evaluate the efficacy of regorafenib in patients with advanced HCC treated in the secondor third-line setting. Methods: In this retrospective and multicenter study, advanced HCC patients not eligible for local therapies, who received a secondor third-line regorafenib therapy after progression on the first-line sorafenib or sequential therapy with chemotherapy (CT) followed by sorafenib, were included. Results: In the first-line setting, 28 (28.9%) patients received CT and 69 (71.1%) patients received sorafenib. There were 24 (24.7%) patients who were intolerant to sorafenib. Disease control rate (DCR) was 53.6% for all patients treated with regorafenib, 62.3% in patients who received regorafenib in the second-line, and 32.1% for those receiving regorafenib in the third-line (p=0.007). Median progression-free survival (PFS) and overall survival (OS) were 5.6 (range; 4.3-6.9) and 8.8 (range, 6.3-11.3) months for all patients treated with regorafenib vs. 7.1 months and 10.3 months for patients who received regorafenib in the second-line vs. 5.1 and 8.7 months for patients who received regorafenib in the third-line, respectively; however, there was no statistically significant difference (p(PFS)=0.22 and p(OS)=0.85). Conclusion: Although receiving CT as a first-line therapy in advanced HCC patients did not affect the survival rates of subsequent regorafenib therapy, it might diminish the DCR of regorafenib.
Keywords: hepatocellular carcinoma; regorafenib; disease control rate; overall survival; chemotherapy; anti-VEGF therapy; SORAFENIB; CANCER